Proceedings of the 4th Workshop on Gender Bias in Natural Language Processing (GeBNLP) 2022
DOI: 10.18653/v1/2022.gebnlp-1.13
|View full text |Cite
|
Sign up to set email alerts
|

Fewer Errors, but More Stereotypes? The Effect of Model Size on Gender Bias

Abstract: The size of pretrained models is increasing, and so is their performance on a variety of NLP tasks. However, as their memorization capacity grows, they might pick up more social biases. In this work, we examine the connection between model size and its gender bias (specifically, occupational gender bias). We measure bias in three masked language model families (RoBERTa, DeBERTa, and T5) in two setups: directly using prompt based method, and using a downstream task (Winogender). We find on the one hand that lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…However, it is interesting to observe that social biases do not necessarily increase with this extra capacity of the MLMs. In the case of gender-related biases, Tal et al (2022) showed that even if the gender bias scores measured on Winogender (Rudinger et al, 2018) are smaller for the larger MLMs, they make more stereotypical errors with respect to gender. However, whether this observation generalises to all types of social biases remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is interesting to observe that social biases do not necessarily increase with this extra capacity of the MLMs. In the case of gender-related biases, Tal et al (2022) showed that even if the gender bias scores measured on Winogender (Rudinger et al, 2018) are smaller for the larger MLMs, they make more stereotypical errors with respect to gender. However, whether this observation generalises to all types of social biases remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…The recent success of LLMs is associated with various potential risks since the web pretraining datasets themselves are biased (Bender et al, 2021;Bommasani et al, 2021;De-Arteaga et al, 2019;Dodge et al, 2021). ; Tal et al (2022) show that the risk of biases gets higher with the increase of the model size, causing biases to resurface during the downstream tasks such as NLI (Poliak et al, 2018;Sharma et al, 2021), coreference resolution (Rudinger et al, 2018;Zhao et al, 2018), and MT (Stanovsky et al, 2019). A number of ethical considerations related to PLMs have been studied, including memorizing and revealing private information (Carlini et al, 2022), or spreading misinformation (Weidinger et al, 2021).…”
Section: Related Workmentioning
confidence: 99%
“…Finally, while the interplay and tradeoff between privacy, efficiency, and fairness in tabular data has received extensive examination (Hooker et al, 2020;Lyu et al, 2020) comparatively fewer studies have been conducted in NLP (Tal et al, 2022;Ahn et al, 2022;Hessenthaler et al, 2022).…”
Section: Introductionmentioning
confidence: 99%